Flat sheet of zinc material as a filter for gamma photons in Tc-99m SPECT imaging - Abdullah, Nazifah; Sayed, Inayatullah Shah; Zakaria, Ahmad (Science Publishing Corporation Publisher of International Academic Journals, 2018)
Purpose of the Study: Scattered gamma photons in single photon emission computed tomography (SPECT) is one of the main issues that degrade the image quality. There are several types of scatter correction methods. However, none of the technique is applied in routine clinical Tc-99m SPECT imaging. Therefore, Zinc (Zn) material filter was constructed for pre-filtration of scattered gamma photons in Tc-99m single photon emission computed tomography (SPECT). Materials and Methods: Tc-99m radioactivity was administered into the Carlson’s phantom. Planar and tomographic data were acquired with and without hot regions insert, respectively, with and without material filter. Scatter to non-scatter ratio was measured from the photopeak region of Tc-99m spectra. Tomographic images were generated using filtered back projection method. Contours on images were drawn with ImageJ software. Images obtained with and without material filter were analysed in terms of detectability of hot regions. Results: Remarkable decrease (≈ 21%) in the ratio of scattered to non-scattered gamma photons with material filter was achieved. Detectability of smaller hot regions with material filter was enhanced. In terms of sizes of all hot regions, material filter results appear closer to the original sizes. Conclusion: Material filter technique could be applied in Tc-99m clinical SPECT, while organ phantom studies are needed.